Mandarin Communication Learning app: A proof-of-concept prototype of contextual learning - Hoe, Tan Wee; Ying, Lin Chia; Yanzhen, Wang (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This paper is an instance of how a Chinese language teacher trainer cooperated with a game-based learning (GBL) researcher to design and develop a mobile application for learning daily communication in Mandarin. The teacher trainer intends to assist beginning learners, specifically those who speak Malay as their first language, to establish confidence in speaking Mandarin in Malaysian‘s daily living contexts; while the researcher has set out to test the ecological validity of a GBL cooperation model. The interdisciplinary cooperation between these individuals has given rise to the production of a Mandarin communication learning application. The key challenge encountered in the development has been to determine the choice of contents and communication contexts for beginning learners. This paper illustrates how the challenges have been resolved and discusses lessons learnt from the cooperation. The outcomes of the study would benefit academics, GBL researchers or developers who plan to initiate cross-disciplinary cooperation towards developing language learning applications.